COMMUNITY BASED OUT OF SCHOOL EDUCATION AND COMMUNITY EMPOWERMENT - Wastuni Wastuni; Nur Apipatin; Jalaludin Jalaludin (STAI Ihyaul Ulum Gresik, 2026)
This study aims (1) to explore the conceptual framework, key principles, and practical applications of community-based out-of-school education within the context of community empowerment; and (2) to examine the various obstacles and opportunities associated with its implementation in promoting self-reliance and sustainable development. Employing a qualitative approach with a literature study design, data were collected through document analysis and processed using triangulation techniques aligned with the analytical principles of Miles and Huberman. Findings reveal that community-based out-of-school education represents a non-formal, participatory, and context-driven learning model that is initiated by and intended for the community itself. Core values such as active involvement, local relevance, empowerment, and adaptability underpin its effectiveness. This model is commonly manifested through skill development initiatives, community learning centers, and targeted empowerment programs that contribute to strengthening local capacities, sustaining cultural heritage, and nurturing social cohesion. Despite its promise, implementation remains challenged by constraints such as insufficient resources, limited community engagement, lack of coordination among stakeholders, and socio-cultural as well as regulatory limitations. However, significant opportunities also exist—such as leveraging strong community networks, utilizing digital technologies, benefiting from supportive policy frameworks at both national and global levels, and aligning with the growing emphasis on sustainability. If implemented with a collaborative, sustained, and community-responsive approach, this educational model holds the potential to become a powerful catalyst for inclusive and resilient local development.